2015
DOI: 10.1128/iai.00137-15
|View full text |Cite
|
Sign up to set email alerts
|

Bistable Expression of CsgD in Salmonella enterica Serovar Typhimurium Connects Virulence to Persistence

Abstract: f Pathogenic bacteria often need to survive in the host and the environment, and it is not well understood how cells transition between these equally challenging situations. For the human and animal pathogen Salmonella enterica serovar Typhimurium, biofilm formation is correlated with persistence outside a host, but the connection to virulence is unknown. In this study, we analyzed multicellular-aggregate and planktonic-cell subpopulations that coexist when S. Typhimurium is grown under biofilminducing conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(96 citation statements)
references
References 90 publications
(126 reference statements)
8
88
0
Order By: Relevance
“…The same pattern of upregulation was observed both in RNA-seq and qRT-PCR assays, and the values of fold change were very close to those in the tested genes. In this study, the tested virulence genes (fimA, marA and soxS) showed lower expression levels in biofilm cells when compared to that in planktonic cells, which is in agreement with a recent finding reported by MacKenzie et al (2015), who observed that the expression levels of virulence genes was enhanced in planktonic cells compared with biofilm cells. …”
Section: Validation Of Gene Expressionsupporting
confidence: 95%
See 1 more Smart Citation
“…The same pattern of upregulation was observed both in RNA-seq and qRT-PCR assays, and the values of fold change were very close to those in the tested genes. In this study, the tested virulence genes (fimA, marA and soxS) showed lower expression levels in biofilm cells when compared to that in planktonic cells, which is in agreement with a recent finding reported by MacKenzie et al (2015), who observed that the expression levels of virulence genes was enhanced in planktonic cells compared with biofilm cells. …”
Section: Validation Of Gene Expressionsupporting
confidence: 95%
“…A similar finding has been observed by MacKenzie et al (2015), who demonstrated that Salmonella biofilm cells had higher expression of csgD/E/F/G, csgB/ A/C, and yaiC when compared to planktonic cells. The function of csg gene-clusters are directly associated with the synthesis of curli fimbriae, which are highly aggregative, non-branching, amyloid-like surface proteins.…”
Section: Discussionsupporting
confidence: 80%
“…6A) and were rdar-like at 37°C, which was consistent with overproduction of curli and cellulose (43). We also observed the phenotypes of each strain grown in liquid culture under biofilm-inducing conditions; cells are known to differentiate into multicellular aggregates (CsgD-ON state) and planktonic cells (CsgD-OFF state) (45,46). Multicellular aggregates were formed in WT cultures and were notably absent in the ⌬csgD strain (Fig.…”
Section: Modular Pcs26 Vectors With Syntheticmentioning
confidence: 49%
“…In vitro models have shown that the dispersed bacteria have unique properties, including increased metabolism (Pettigrew et al ., ; Guilhen et al ., ), increased invasion/killing abilities against epithelial cells (Marks et al ., ), increased killing abilities against macrophages (Chua et al ., ) and increased escape abilities against phagocytosis (Chua et al ., ). The increased virulence properties of the dispersed bacteria have been shown in murine model (Uppuluri et al ., ; Pettigrew et al ., ; MacKenzie et al ., ) and Caenorhabditis elegans model (Chua et al ., ). The dispersed bacteria have also a predisposition to colonize new environments due to the simultaneous presence of individual cells and multicellular aggregates that confers a fitness advantage to the dispersal population in a wide variety of environments (Kragh et al ., ; Cogan et al ., ).…”
Section: The Dual‐role Of the Dispersal Process In Virulencementioning
confidence: 99%